Urban stormwater flood management in the Cordeiro watershed, São Paulo, Brazil: does the interaction between socio‐political and technical aspects create an opportunity to attain community resilience?. Issue 3 (18th June 2015) - Borba, M.L.; Warner, J. F.; Porto, M. F. A.
Abstract: In the urban Cordeiro watershed, São Paulo, Brazil, the impervious surface has reduced stormwater infiltration and the drainage system has become insufficient. Engineering firms have been contracted, under government supervision, to implement the construction of six water reservoirs in order to decrease the frequent flood events in the watershed. The main purpose of this article is to contribute to the study of the relationship between technical and socio‐political aspects of urban stormwater drainage, as technical solutions alone have proven to be insufficient. Research conducted in the area shows that residents and businessmen construct individual infrastructure to protect their homes and businesses, independent of any interaction with engineering firms or local government officials. Relevant literature suggests that stronger interaction among these stakeholders offers an opportunity to evolve from self‐reliance into a collective strategy of resilience, enhancing the effectiveness of flood risk management practices.